The Effectiveness of Handicrafts on Anxiety Reduction among Hospitalised Children in Paediatric Ward of Dhulikhel Hospital - Ranamagar, Binita; Karki, Sita (Journal of Nepal Paediatric Society, 2021)
Introduction: Disease and hospitalization can be the first crisis which a child encounters. It can cause acute anxiety to them which may sequel their uncooperative behavior to the treatment procedures. Furthermore, high level of anxiety if persisted for longer period can affect their physiological and psychological health. So, in order to deal this anxiety beforehand, handicraft has become an effective play intervention in the hospital. Hence, we conducted this study to investigate the effectiveness of handicrafts on anxiety reduction among hospitalized children. Method: This is a pre-experimental study administered to 30 admitted children in Paediatric Ward of Dhulikhel Hospital who were selected using consecutive sampling technique. Anxiety levels before and after intervening handicraft were assessed via interview using State-Trait Inventory of Cognitive and Somatic Anxiety - Child Version (STICSA-C) tool where intervention was making handicrafts with colorful paper as per children’s capacity and preference for total six times in two consecutive days at four hours interval. Results: The study showed significant difference between anxiety score before and after intervening handicraft (42.70 ± 10.60 Vs. 33.30 ± 8.70, p = < 0.001). While, anxiety level before intervening handicraft was not significantly associated with the selected demographic and clinical variables of children. Conclusions: In the study, handicraft was an effective play material in reducing anxiety among hospitalized children. But it is necessary to perform further studies that will take into account greater methodological stringency.